Rare Opportunities for Insights Into Serotonergic Contributions to Brain and Bowel Disorders: Studies of the SERT Ala56 Mouse - Stilley, Samantha E.; Blakely, Randy D. (Frontiers in Cellular Neuroscience, 2021)
Altered structure, expression, and regulation of the presynaptic serotonin (5-HT) transporter (SERT) have been associated with multiple neurobehavioral disorders, including mood disorders, obsessive-compulsive disorder (OCD), and autism spectrum disorder (ASD). Opportunities to investigate mechanistic links supporting these associations were spurred with the identification of multiple, rare human SERT coding variants in a study that established a male-specific linkage of ASD to a linkage marker on chromosome 17 which encompassed the location of the SERT gene (SLC6A4). We have explored the most common of these variants, SERT Ala56, in vitro and in vivo. Results support a tonic elevation of 5-HT transport activity in transfected cells and human lymphoblasts by the variant in vitro that leads to an increased 5-HT clearance rate in vivo when studied in the SERT Ala56 mouse model, along with altered sensitivity to SERT regulatory signaling pathways. Importantly, hyperserotonemia, or an elevated whole blood 5-HT level, has been reported in SERT Ala56 mice, reproducing a well-replicated trait observed in a significant fraction of ASD subjects. Additionally, we found multiple biochemical, physiological and behavioral alterations in the SERT Ala56 mice that can be analogized to those observed in ASD and its medical comorbidities. The similarity of the functional impact of the SERT Ala56 variant to the consequences of p38 MAPK activation, ascribed to the induction of a biased conformation of the transporter toward an outward-facing conformation, has resulted in successful efforts to restore normal behavioral and bowel function via pharmacological and genetic p38 MAPK targeting. Moreover, the ability of the inflammatory cytokine IL-1 to enhance SERT activity via a p38 MAPK-dependent pathway suggests that the SERT Ala56 conformation mimics that of a chronic inflammatory state, supporting findings in ASD of elevated inflammatory cytokine levels. In this report, we review studies of the SERT Ala56 variant, discussing opportunities for continued insight into how chronically altered synaptic 5-HT homeostasis can drive reversible, functional perturbations in 5-HT sensitive pathways in the brain and periphery, and how targeting the SERT regulome, particularly through activating pathways such as those involving IL-1/p38 MAPK, may be of benefit for neurobehavioral disorders, including ASD.